Self-defeating and self-esteem among a sample of displaced adolescents in the City of Swaida. (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current research aimed to identifying the relationship between self-defeating and self-esteem among displaced adolescents, and to identifying the differences in self-defeating and self-esteem depending on the gender variable. And it aimed to identifying the differences between high self-defeating and low self-defeating  in self-esteem, Where the sample of the study was 217 adolescent displaced persons within the city of Swaida. The two measures that were applied are the self-defeating scale prepared by Abu Halawa (2013) after being adapted to the research sample, and the self-esteem prepared by Bouamour (2018) after being adapted to the research sample. The results showed that there is an inverse relation between self-defeating and self-esteem. And it showed statistically significant differences on the self-defeating scale according to the gender variable in favor for males. The results also indicated that there were statistically significant differences in the self-esteem according to the gender variable in favor of males. And the results showed statistically significant differences between high and low self-defeating in self-esteem in favor of low self-defeating who show higher levels of self-esteem.